TINDAKAN REPRESIF APARAT PENEGAK HUKUM (KEPOLISIAN) TERHADAP AKSI DEMONSTRASI MASSA DI WILAYAH HUKUM NUSA TENGGARA BARAT - APRIANI, TITIN (Universitas Mahasaraswati K. Mataram, 2024)
The aim of this research is to find out how repressive the police officers acted towards the masses during the demonstrations and what factors were the obstacles for the police officers in dealing with the masses while the demonstrations were taking place. This research is library research, namely using data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is by collecting various ideas, theories and concepts from various literature which focuses on the process. comparison between propositions, articles or other laws. The approach methods used in this research are the statutory approach, the conceptual approach and the case approach. The results of the research show that the actions of the police towards the masses who were protesting often occurred repressive actions and this happened because the police sometimes had several obstacle factors that could not be handled directly because the demonstrators often went on a rampage and inevitably the law enforcers, especially the The police often spontaneously carry out repressive actions against the masses and exceed the applicable provisions and regulations.